Topical issues of stimulating the work of civil servants - A. O. Ivanov (Law and Safety)
Emphasis is placed on the fact that one of the topical and urgent issues of reforming the system of public administration in Ukraine in general and the institution of civil service in particular is to improve the mechanism of stimulating the work of civil servants. It is noted that the approach chosen by the official authorities to improve the effectiveness of incentives for civil servants is limited mainly to the revision of approaches to their remuneration. At the same time, such important elements of the mechanism of stimulating employment, such as guaranteed career growth, protection from administrative pressure and illegal disciplinary action, guaranteed application of incentives and rational organization of the work process, do not receive due attention and development. It is emphasized that one of the problems of improving the incentives for civil servants is the lack of a clear understanding of the nature and objectives of incentives, its relationship with such phenomena as motivation and encouragement of employees.